Pengaruh Good Corporate Governance dan Corporate Sosial Responsibility terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Mediasi pada Perusahaan Misscellaneous Industry di BEI Periode 2016-2019 - Metalaras Saputri; Yuyun Isbanah (Jurnal Ilmu Manajemen, 2021)
This study aims to determine the effect of good corporate governance (GCG) and corporate social responsibility (CSR) on companies' value with financial performance listed on the IDX for the 2016-2019 period. This research's object is 19 selected companies in various industrial sectors, with a sample of 76 annual reports that meet the criteria. The data used is the 2016-2019 annual report. The method used is the classical assumption method, multiple linear regression, path analysis method using SPSS version 25. The direct effect study results, GCG, an agency composed of management ownership, institutional ownership, and the board of directors, will not significantly impact the value of the company. GCG, which is proxied by the audit committee and CSR, affects firm value and financial performance (ROA), affecting firm value. The indirect effect research shows that ROA has not been able to mediate the effect of GCG, which is proxied by managerial ownership, institutional ownership, and commissioners' board.ROA is only able to mediate the effect of CSR on firm value.